Combinations of Oseltamivir and T-705 Extend the Treatment Window for Highly Pathogenic Influenza A(H5N1) Virus Infection in Mice - Marathe, Bindumadhav M. (Sci Rep, 2016)
Current anti-influenza therapy depends on administering drugs soon after infection, which is often impractical. We assessed whether combinations of oseltamivir (a neuraminidase inhibitor) and T-705 (a nonspecific inhibitor of viral polymerases) could extend the window for treating lethal infection with highly pathogenic A(H5N1) influenza virus in mice. Combination therapy protected 100% of mice, even when delayed until 96 h postinoculation. Compared to animals receiving monotherapy, mice receiving combination therapy had reduced viral loads and restricted viral spread in lung tissues, limited lung damage, and decreased inflammatory cytokine production. Next-generation sequencing showed that virus populations in T-705–treated mice had greater genetic variability, with more frequent transversion events, than did populations in control and oseltamivir-treated mice, but no substitutions associated with resistance to oseltamivir or T-705 were detected. Thus, combination therapy extended the treatment window for A(H5N1) influenza infection in mice and should be considered for evaluation in a clinical setting.